Transformer species in the flora of the Starobilsk grass-meadow steppe (Ukraine) - Kucher, Oksana O. (Biodiversity: Research and Conservation, 2016)
The results of an investigation of alien species that change the character, condition, form or nature of ecosystems over large areas (transformer species) in the flora of the Starobilsk grass-meadow steppe are presented. The check-list of alien plants includes over 386 species of vascular plants, of which 28 are invasive and 6 are transformer species. In this study, the data on the first records of alien species, their distribution history, ecology, occurrence in different plant communities and degree of naturalization were compiled. The distribution maps of transformer species are provided.